Relationship Between Nutritional Status and HbA1c Levels in Diabetes Patients at Primary Health Center in Kupang City - Veronika Florida Fiani; Elisabeth Levina Setianingrum; Rahel Rara Woda; Kristian Ratu (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Diabetes Mellitus (DM) is a non-communicable disease with an increasing global prevalence. Effective monitoring and management are essential to reduce disease burden and prevent complications, including through HbA1c assessment and nutritional status evaluation such as Body Mass Index (BMI) and Mid-Upper Arm Circumference (MUAC), which are feasible in primary health care settings. This study aimed to analyze the relationship between nutritional status and HbA1c levels among patients with Diabetes Mellitus at primary health centers in Kupang City. A cross-sectional design was conducted among 69 respondents selected using consecutive sampling at Oepoi, Sikumana, and Bakunase Primary Health Centers. Data were collected through BMI and MUAC measurements and HbA1c examination and analyzed using Pearson correlation test. The results indicated that most respondents were female, overweight based on BMI, had normal MUAC, and uncontrolled HbA1c levels. Statistical analysis showed no significant association between BMI and HbA1c levels (p > 0.05) nor between MUAC and HbA1c levels (p > 0.05). In conclusion, nutritional status was not significantly associated with HbA1c levels among DM patients. Glycemic control may be influenced by factors beyond anthropometric indicators.